2015
DOI: 10.3928/01477447-20150701-51
|View full text |Cite
|
Sign up to set email alerts
|

Safe Cosmetic Leg Lengthening for Short Stature: Long-term Outcomes

Abstract: It is well known that limb lengthening is performed to treat limb-length discrepancies resulting from congenital anomalies and developmental problems. However, few studies discuss lengthening for cosmetic purposes. The current authors conducted a prospective study with long-term follow-up. From July 2002 through June 2007, 133 patients requested that their height be increased. Fifty-two were approved to undergo limb-lengthening surgery. Two were lost to final follow-up, leaving 50 in the study group. For all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Cosmetic stature lengthening resulted in improved self-esteem and quality of life, and decreased distress and shyness levels. 5 - 7 , 11 , 12 , 16 - 19 Most patients reported high satisfaction rate and felt they would recommend the surgery for others with short stature. 5 , 6 , 17 Satisfaction, however, might not be predictable in patients with body dysmorphic disorder or dysmorphophobia.…”
Section: Discussionmentioning
confidence: 99%
“…Cosmetic stature lengthening resulted in improved self-esteem and quality of life, and decreased distress and shyness levels. 5 - 7 , 11 , 12 , 16 - 19 Most patients reported high satisfaction rate and felt they would recommend the surgery for others with short stature. 5 , 6 , 17 Satisfaction, however, might not be predictable in patients with body dysmorphic disorder or dysmorphophobia.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 9 Studies that utilised the Ilizarov external device found complication rates ranging from 37 to 70%, coupled with reoperation rates at 28 to 35%. 8 , 13 …”
Section: Urrent S Tate Of S Tature L Engtheningmentioning
confidence: 99%
“…Qualitative outcome measures based on height gain and the presence/absence of complications found that most patients obtain excellent results, although some have been noted to have only good or satisfactory results. 8 , 13 In the backdrop of risks and complications associated with stature lengthening, patients report high rates of satisfaction with the result along with improvements in self-esteem and self-confidence. 1 , 8 , 10 , 11 , 13 They would also undergo the procedure again and recommend it to others.…”
Section: Urrent S Tate Of S Tature L Engtheningmentioning
confidence: 99%
See 1 more Smart Citation